2020
DOI: 10.1186/s12935-020-01696-9
|View full text |Cite
|
Sign up to set email alerts
|

Musashi-1 promotes cancer stem cell properties of glioblastoma cells via upregulation of YTHDF1

Abstract: Background Glioblastoma (GBM) is the most lethal brain tumor characterized by high morbidity and limited treatment options. Tumor malignancy is usually associated with the epigenetic marks, which coordinate gene expression to ascertain relevant phenotypes. One of such marks is m6A modification of RNA, whose functional effects are dependent on the YTH family m6A reader proteins. Methods and results In this study, we investigated the expression of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 38 publications
1
43
0
Order By: Relevance
“…As a reversible epigenetic modification, m6A is associated with the occurrence, metastasis, and drug resistance of tumors (Huang et al 2020). YTHDF1 plays an essential role in a variety of cancers as a core factor of RNA methylation modification (Yarmishyn et al 2020;Zhang et al 2020). However, its specific mechanism in PCa has not been defined.…”
Section: Discussionmentioning
confidence: 99%
“…As a reversible epigenetic modification, m6A is associated with the occurrence, metastasis, and drug resistance of tumors (Huang et al 2020). YTHDF1 plays an essential role in a variety of cancers as a core factor of RNA methylation modification (Yarmishyn et al 2020;Zhang et al 2020). However, its specific mechanism in PCa has not been defined.…”
Section: Discussionmentioning
confidence: 99%
“…YTHDF2 has been found to regulate glucose metabolism via the stabilization of the proto-oncogene MYC in glioblastoma stem cells ( Dixit et al, 2020 ). Elevated YTHDF1 was associated with poor prognosis as it is thought to promote the proliferation and migration of glioblastoma cells ( Yarmishyn et al, 2020 ). HNRNPC contributes to glioma progression although the mechanisms underlying this association are not yet known ( Wang L.C.…”
Section: A In Brain Disordersmentioning
confidence: 99%
“…Prospectively, MSI1–directed post–transcriptional control of gene expression could become even more complex involving RNA modifications, such as m6A (N6–methyladenosine), becoming more critical for cancer development [ 24 ]. In this view, it was previously shown that MSI1 promotes cancer stem cell properties of glioblastoma cells via upregulation of the m6A reader YTHDF1 (YTH N6–methyladenosine RNA–binding protein 1) [ 25 ].…”
Section: Musashi–1—a Conserved Stemness Rbp With Unique Functionsmentioning
confidence: 99%
“…The functional impact of MSI1 in cancer was studied on the basis of loss– as well as gain–of function studies, including shRNA–, siRNA–, morpholino–directed impairment of MSI1 abundance and its overexpression [ 14 , 19 , 22 , 23 , 25 , 47 , 65 , 69 , 75 ]. Despite technical limitations and flaws of individual studies, there is an overarching agreement in that MSI1 is a potent regulator of various cancer hallmark pathways such as proliferation, apoptosis, anoikis resistance and self–renewal, migration, invasion and EMT (epithelial–mesenchymal transition), as well as tumor growth in vivo.…”
Section: Msi1 As a Modulator Of Cancer Hallmarksmentioning
confidence: 99%
See 1 more Smart Citation